Reading Practices in Portuguese Language from BNCC: what are they based on and how to proceed inside the classroom? - Rossi, Maria Aparecida Garcia Lopes (Linha D’Água, 2021)
The National Common Core Curriculum – BNCC (BRASIL, 2018) determines the pedagogical reading practices to be developed in basic education. However, this official curricular document does not clarify the theoretical foundation for the axis of reading in Portuguese language classes. Therefore, there is a lack of theoretical support for the teacher’s planning of reading practices. In this scenario, this research aims to investigate the axis of reading proposed by the BNCC regarding Portuguese language, from the sixth to the ninth grade, in terms of the document’s proposal, its theoretical bases and the didactic possibilities of its key concepts. Methodologically, this is a qualitative research of documental and bibliographical approach. The results of the analyses offer subsidies, so that the Portuguese language teacher can prepare theory-based reading activities.